Mobile app prototype for course management in secondary education - Andrade Arenas, Laberiano Matías (2023)
In the last decade, mobile applications have proven to be con-stantly evolving where it has played an important role since the development of technology. Children and adolescents are very interested in these new technolo-gies, and it is easier for them to use them, which also helps them to learn any subject of their interest. That is why in this research a mobile application proto-type is designed for the management of courses in secondary education. The Scrum methodology was used to develop its phases. As a result, a proposal arose to develop a prototype of a mobile application to improve student learning. The survey result shows that most of the questions have a high rating scale, with the highest average being 4.91 with a standard deviation of 0.302, and only a low rating scale of 1.45, on average, with a standard deviation of 0.52. The study is scalable, where it can be applied to university education. The beneficiaries are the educational communities.